A real time Fast Fourier Transform analyser - Fisher, John Stanley (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1980)
From the requirements of the Ionosonde digitisation project, undertaken by Rhodes University Antarctic Research Group, it was decided to use the Fast Fourier Transform to compute the spectrum analysis. Several FFT algorithms are reviewed and properties discussed, and the Ccoley Tukey algorithm chosen for utilization. The hardware implementation of this algorithm, and the microprogram control of the whole system are discussed in detail, and such design aspects that required computer simulation are also treated in detail. The final testing of the analyser is shown, and includes a test using data from an ionosonde sounding. The conclusions contain details of extensions to the analysers present operation, required by plans to place the whole Chirpsounder under microprocessor control
Keywords: Fourier transformations; Ionosondes; Algorithms; Computer simulation